A mixed method evaluation of economic and environmental considerations in construction transport planning: The case of Ostlänken. (June 2021) - Fredriksson, Anna; Nolz, Pamela C.; Seragiotto, Clóvis
Highlights: Scenario analysis of the relationship between storage location and transport efficiency. A framework for infrastructure contract planning handling. A mixed methods approach for site layout planning in infrastructure development. Abstract: Among the construction related transports, the transport of soil and rock materials stand for a major part. The purpose of this study is to develop an approach enabling scenario analysis of the relation between storage location and soil and rock material transport planning. The study follows a sequential exploratory mixed methods design. First a literature review and a qualitative case study identifies the problem. Second a quantitative optimization method is used to evaluate possible scenarios showing the interdependence between storage location costs and transport impact. The study has two main contributions, the mixed methods approach to evaluate economic and environmental considerations in an infrastructure project and the scenario analysis of different options for inventory control and transport. The presented study adds knowledge to transport efficiency of rock and soil materials.